Performa Produksi dan Analisis Usaha Puyuh (Coturnix coturnix japonica) yang diberi Substitusi Black Soldier Fly Larvae (BSFL) pada Pakan Komersil - Fithria Nisa Hanifah; Koesnoto Soepranianondo; Soeharsono Soeharsono; Anam Al Arif; Widya Paramita Lokapirnasari; Nenny Harijani; Siti Hadijah; Mariana Ruth Theresia Hutabarat (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2019)
Black Soldier Fly Larvae (BSFL) is an alternative protein source for livestock. This research aimed to know the effectiveness of BSFL for commercial feed substitution, related to production, productivity, and profitability in quail farm. This study used 80 quails which divided into 4 groups and each group consist of 20 quails. The treatments contained BSFL substitution with different composition, control group (P0) was given 100% commercial feed, (P1) was given a 5% BSFL substitution, (P2) was given a 10% BSFL substitution and (P3) was given a 20% BSFL substitution. Contribution margin (CM) analysis was used to determine the yields of the groups in this study. Results showed that the highest feed consumption rate is in P3, production (egg in total and weight), productivity and yields in P3 is the highest, although there's no difference between P0, P2 and P3 based on the analysis MANOVA. BSFL substitution at 20% is recommended to the farmers to increase profits.